Diagnosing and analyzing the entrepreneurial mindset according to the Hermann scale of creative thinking: A case study in the Training and Development Department - General Secretariat of the Iraqi Council of Ministers - Alubad, Sanaa A.; Almusawi, Adham D. (International Journal of Psychosocial Rehabilitation, 2020)
The volatile world of business is witnessing the emergence of novel concepts regarding the mechanisms of competition between companies and existing organizations and those wishing to enter the labor market. Researchers in this field can be regarded as being responsible for clarifying these concepts and their impact, as well as elucidating their characteristics, dimensions and methods of measurement. It is possible to consider entrepreneurship as one of the most prominent matters in the field at the moment, with several domains that have attracted wide attention at the present time. Perhaps the most important one is the subject of the entrepreneurial mindset; this study intends to shed light on this topic due to the scarcity of work by Arab researchers in this field. This research presents a simplified method for measuring the entrepreneurial mindset based on Hermann's measure of brain dominance, combining it with the principles of creative thinking and brain preferences which may open the way for future research in this field. The research provides a conceptual framework for both the entrepreneurial mindset and the Hermann Brain Dominance Scale, which was adapted as a checklist that was used in the Prime Minister's Training and Development Department on members of senior management to measure the extent to which individuals possessed the entrepreneurial mindset by using the parts of the brain responsible for creativity. The results showed that the participants possessed a variety of brain preferences, with only a small gap in levels of creative thinking detected. These findings suggest that the entrepreneurial mindset can be developed by focusing on non-applied matters and creative features skills.